Interprofessional team-based placements: The importance of space, place, and facilitation. - Brewer, Margo; Flavell, Helen; Jordon, J. (Informa Healthcare, 2017)
Interprofessional education in practice settings typically requires greater resource investment than in the classroom or online. Increased interest in return on investment means research on the outcomes of practice-based interprofessional education is needed. In this article, we report findings from a qualitative study involving a series of focus groups with health sciences' students during their interprofessional placements in three community health settings in Western Australia. An exploratory case study approach was adopted to determine students' perceptions of the placement and their learning. The presage-process-product (3P) model of learning and teaching was employed to illuminate to the nature of this interprofessional education experience. Verbatim transcripts were analysed by two researchers using an inductive approach to derive key themes. Findings illuminate a number of factors that strongly influenced student perceptions of their learning in interprofessional practice-based placements including a dedicated space to collaborate and learn; exposure to a wide range of professions in practice settings; the approach of the facilitators; and students' previous clinical experience, year level and the timing of the placement. Students reported that the placement enhanced their knowledge, professional communication, leadership, understanding of other health professions and collaboration. This study provides contemporary insight into key factors that influence student learning during practice-based interprofessional placements.